Prevalence and multidrug resistance of Staphylococcus aureus in the hospitals of Gulbarga and Raichur districts - D, Ramakrishna (Recent Research in Science and Technology, 2012)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> A study to investigate the multidrug resistance of Staphylococcus aureus to conventional antibiotics being frequently used in these regions. Methicillin resistance Staphylococcus is pathogenic and is an important nosocomial organism. We report the prevalence and antimicrobial susceptibility pattern of MRSA is major in northern districts of Karnataka.Â  200 samples from variety hospitals in Gulbarga using standard microbiological techniques. 25 isolates are coagulase positive Staphylococcus aureus. Almost all isolates of MRSA 95% were resistant to amphicillin, 93.2% penicillin, 75% amoxicillin, 72% gentamycin, 70% erythromycin respectively; multidrug resistance was observed and suggests possible abuse of these drugs. Poor hospital attendance and the need for better enlightment campaign against the use of drug without prescriptions.Â 